The Effect of Music Therapy for Improving Quality of Life in Patients with Cancer Pain: An Evidence Based Case Report - Yanuar Ardani; Ibrahim Achmad; Edward Faisal; Vinandia I Poespitasari; Rudi Putranto; Hamzah Shatri (Interna Publishing, 2023)
Background: Music therapy is a frequently used complementary and creative arts treatment in psychosocial cancer care. Particularly in advanced cancer populations and palliative care, music therapy has recently received high attention in both research and clinical care. This evidence-based case report is aimed to assesed the effect of music therapy for improving quality of life in patients with cancer pain. Methods: the search was conducted on Pubmed, Cochrane Library, and EMBASE according to clinical question. The studies were selected based on inclusion and exclusion criteria. The selected study was critically appraised. Results: All selected studies significantly showed effectiveness of music therapy towards quality of life in cancer patient. Conclusion: Music therapy might be beneficial adjuvant for cancer patients.